The neuroprotective effects of β-hydroxybutyrate on Aβ-injected rat hippocampus in vivo and in Aβ-treated PC-12 cells in vitro. (February 2015) - Xie, G.; Tian, W.; Wei, T.; Liu, F.
Abstract Alzheimer's disease is a neurodegenerative disorder associated with the deposition of the peptide amyloid-beta (Aβ) in senile plaques and cerebral vasculature. The neurotoxic mechanisms of this condition have been linked to oxidative-stress-induced apoptosis leading to widespread neuronal loss. Herein, we demonstrate the neuroprotective effects of a ketone body D-β-hydroxybutyrate (β-HB) in neural cell lines and an animal model induced by injecting Aβ into the hippocampus. Using histological examination and the TUNEL assay, we show that administration of exogenous β-HB effectively prevents Aβ deposition and neuron apoptosis in this rat model. β-HB pretreatment also relieves the oxidative stress in Aβ-induced PC-12 cells, as shown by decreased intracellular reactive oxygen species and Ca2+ levels, activated Nrf2 and recovered superoxide dismutase and catalase activities. Consequently, the apoptotic pathway is also inhibited in these cells, with decreased levels of p53, caspase-12, caspase-9, caspase-3; a decreased Bax/Bcl-2 ratio; and decreased cytochrome c release. Taken together, our study provides a molecular basis for the neuroprotective effects of β-HB in line with the suppression of oxidative stress and the inhibition of apoptotic protein activation.